Analisis Pelaksanaan Evaluasi Formatif dan Evaluasi Sumatif dalam Pembelajaran Matematika di SMK N 6 Padang - Vica Aulia Zetra; Nita Putri Utami (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Learning evaluation plays a central role in ensuring the success of the educational process, especially in mathematics learning at Vocational High Schools (SMK) that require integration between theory and practice. This study aims to comprehensively analyze the implementation of formative and summative evaluations at SMK N 6 Padang. Using a descriptive qualitative approach, data was obtained through observations, in-depth interviews, and document analysis. The results show that formative evaluations are carried out systematically through essay tests, contextual quizzes, discussions, and observations of student participation. This evaluation can monitor learning progress, encourage active engagement, and strengthen students' conceptual understanding. Meanwhile, summative evaluations are consistently applied using multiple-choice questions that encompass low-order thinking skills (LOTS) to high-order thinking skills (HOTS). in line with the learning objectives and curriculum. Both forms of evaluation have proven to be very effective, based on teacher observations and feedback. Although not all aspects were followed up explicitly, the assessment mechanisms applied reflect the principles of modern evaluation that are adaptive, fair, and competency-based. It can thus be concluded that the evaluation is running very effectively at 88.88%, and the evaluation implementation at SMK N 6 Padang not only succeeded in measuring student achievement but also became an instrument to strengthen the quality of learning relevant to the demands of industry and the developments in 21st-century education.